Exchange rate pass-through in emerging Asia and exposure to external shocks - John Beirne; Nuobu Renzhi; Pradeep Panthi (Asian Development Bank Institute (ADBI), 2023)
Using a time-varying parameter SVAR model over the period 1994 to 2021, this paper provides estimates of exchange rate pass-through (ERPT) to both producer and consumer prices for nine emerging Asian economies. We also examine the role of four global shocks as propagation channels to both producer and consumer price ERPT, specifically via oil prices, global output, US monetary policy, and the VIX. Our main findings are: (i) ERPT is incomplete and mostly higher for ERPT to producer than consumer prices; (ii) longer-term ERPT to producer and consumer prices is mostly greater in magnitude than shorter-term ERPT; (iii) ERPT has been declining for most Asian EMEs since around 2010; (iv) oil price and global output shocks mostly affect longer-term producer price ERPT in emerging Asia; and (v) US monetary policy and VIX shocks mostly affect longer-term consumer price ERPT in emerging Asia.
Keywords: E31; F31; F41; 330; exchange rate pass-through; global shocks; structural VAR; time-varying parameter VAR